Regional Differences in Disability and Its Influencing Factors among Middle-aged and Elderly People in East, Central and West Major Regions in China - LIU Ying, JIANG Juncheng, JING Huiquan (Zhongguo quanke yixue, 2024)
Background The aging of our population and the intensification of major chronic disease problems will inevitably lead to an increase in the number of disabled people, resulting in increased pressure on social care and a heavier burden on the government and families for the elderly. At the same time, the unbalanced allocation of health resources will pose even more serious challenge to the medical treatment and nursing care of the disabled population. Objective To explore the differences of disability rate, disability degree and influencing factors among middle-aged and elderly people in eastern, central and western regions of China. Methods Data from the 2018 China Health and Retirement Longitudinal Study (CHARLS) were analyzed from 2022-10-05 to 2023-01-13, and 19 170 middle-aged and elderly people aged 45 years and above were selected as the study subjects. Activities of daily living (ADL) and instrumental activities of daily living (IADL) scales were used to determine disability. The situation and degree of disability in middle-aged and elderly people were considered as dependent variables, and independent variables were selected from three aspects of general demographic characteristics, health evaluation and lifestyle according to CHARLS data questionnaire. Binary and multivariate Logistic regression analyses were conducted to analyze the factors affecting the disability and degree of disability of middle-aged and elderly people in eastern, central and western regions of China. Results Comparison of the rate and degree of disability among middle-aged and elderly people in eastern, central and western regions showed statistically significant differences (χ2=143.014, P<0.001; χ2=136.356, P<0.001) . Mild disability predominated among middle-aged and elderly people in eastern, central and western regions; the difference was statistically significant when comparing the age composition of middle-aged and elderly people with mild and severe disability in eastern, central and western regions (P<0.05) . There were commonalities and characteristics in the influencing factors of disability and disability degree in the three regions. Age, education level and self-rated health status were the common influencing factors of disability in middle-aged and elderly people in eastern, central and western regions (P<0.05) . Gender and physical disability were the independent influencing factors for the development of disability in middle-aged and elderly people in eastern China (P<0.05) . The risk of disability in middle-aged and elderly people in females was 86.0% higher than that in males (OR=1.860, 95%CI=1.036 to 3.338) . Marital status and combining with chronic disease were the independent influencing factors for disability in middle-aged and elderly people (P<0.05) . Residence, brain damage/intellectual impairment were the independent influencing factors for disability among middle-aged and elderly people in western China (P<0.05) . Conclusion In order to solve and improve the differences of disability status among the middle aged and old people in the eastern, central and western regions of China, individualized prevention and intervention strategies for different regions should be developed according to the differences of influencing factors, regional medical services and rehabilitation guidance should be provided, and a cross-regional allocation mechanism of medical and health resources should be established to promote regional healthy and sustainable development.